AWARENESS OF HEALTH CARE WORKERS TOWARDS ANTI-OBESITY MEDICATIONS IN A SAMPLE OF HOSPITALS IN AL-DIWANIYAH PROVINCE, IRAQ - Sattar Abdul Ameer Merhej; Abeer Ghazie Al Sawafi (Journal of Medical Genetics and Clinical Biology, 2024)
Background: The most common medical condition in low-, middle-, and high-income countries is obesity. Thus, diet, lifestyle, and anti-obesity drugs are becoming popular adjuvant treatments for this medical condition. Knowing the community's opinion and awareness is crucial. Materials and methods: This cross-sectional study was conducted at Al-Diwaniyah province hospitals. A convenience sample of 200 health care workers in Al-Diwaniyah province hospitals who are enrolled in the three hospitals (Al-Diwaniyah teaching, the general Al-Hamiza, and the general Al-Shamia). This study includes health care workers (HCWs) of both genders and ages over 20 years of morning shift. While this study excludes those with an educational level below secondary school, administrative staff were excluded from the study. The data collect started from the 3rd of November 2023 till the 13th of February 2024. Results: The results of this study indicate that 52.5% of health workers have a moderate awareness score, followed by 24.5% of the participants have a poor awareness score, and only 23.0% of HCWs have a good awareness score. the results of this study reveal that there is significant relationship between demographic characteristics and overall awareness score (P. value <0.05), except for residence. Conclusions: The study report that most HCWs have a moderate awareness about anti-obesity drugs. These results explain that old age, males’ gender, high education and physician have good assessment scores for awareness about anti-obesity drugs. The study recommends developing and focusing on community-based educational programs and campaigns on anti-obesity medications to improve their views on obesity management.